Pengembangan Game Ular Tangga dengan Kartu Baca Untuk Meningkatkan Kemampuan Membaca Permulaan Kelas 2 SD Plosojenar - Shinta Meyza Putri; Anisa Surya Kartika; Erdea Widiyani; Rani Setiawaty (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The aim of this research is to develop and determine the feasibility of learning media in the form of snakes and ladders in class 2 of SD N Plosojenar. This research uses the Borg and Gall model, which is a method or step for creating new products or developing and perfecting existing products. The subjects of this research were 13 grade 2 students at SD N Plosojenar. Data collection techniques include observation, interviews, pre and post test methods, as well as teacher and student responses. The type of data is qualitative and quantitative data which contains evaluation category criteria to determine product suitability. The results of this research are as follows: 1). Snakes and Ladders media was also developed. 2). The teacher's response to snake media was with a score of 4.82. Based on calculations based on the teacher's response, it can be concluded that the snakes and ladders game media is "very feasible" and the students' response to the snakes and ladders media is an increase in students' interest in participating in learning. 3) The students' pretest score obtained an average of 50 and after being given treatment the posttest score increased to an average of 74.09. In the same pre and post test there was an increase in learning outcomes of 24.09. Thus, Snakes and Ladders for grade 2 students at SDN Plosojenar was declared suitable for use and could improve their early reading skills in grade 2.